A retrospective review of chemo-radiation in anal carcinoma - Mark, Yael (My University, 2017)
Introduction In South Africa, in 2007 there were 139 new cases of anal cancer. This malignancy shows a female predominance and is associated with several risk factors including smoking and infection with Human Immunodeficiency Virus and Human Papilloma Virus. The standard of care for the treatment of localised anal cancer is concurrent chemo-radiation. The purpose of this retrospective study was to describe the patient characteristics and the treatment toxicity of chemo-radiation in patients with localized squamous cell anal cancer. A further aim was to describe the treatment outcomes. Materials and Methods A total of 64 patients with anal carcinoma, who presented to the department of radiation oncology at Charlotte Maxeke Johannesburg Academic Hospital between 2006 and 2012, were included in the study. Only squamous cell carcinoma histological subtypes of anal carcinoma qualified for inclusion in the study. Patients with metastatic anal carcinoma were excluded from the study. Data about patient and tumour characteristics, treatment toxicities and treatment response were captured in a proforma sheet. Once data collection was complete, statistical analysis using the SAS software package was carried out. Results The median age at first consultation was 48 years. Sixty-seven per cent of the study group was female. Sixty-eight per cent of patients presented with advanced tumours (T3/T4) and 60% of the patients had node positive disease. Fifty per cent of patients were Human Immunodeficiency Virus positive with a median cluster of differentiation 4 (CD4) cell count of 250 cells/mm3. The predominant adverse effects were skin toxicity in 81% of patients and pain in 75% of patients. Thirty-eight per cent of patients who followed-up after treatment completion experienced a tumour recurrence at a median duration of 303 days after treatment. The progression free survival estimates at 12 months were 85% and at 24 months were 46%. Conclusion The patient population presenting to Charlotte Maxeke Johannesburg Academic Hospital radiation oncology department was predominantly comprised of middle aged females with advanced stages of anal carcinoma. Approximately half of these patients were Human Immunodeficiency Virus positive. Skin toxicity and pain were the commonest adverse effects observed. There was a high recurrence rate noted, likely due to the fact that most patients presented with advanced disease.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Radiation Oncology Johannesburg 2017.
Keywords: Anus Neoplasms (Anal Carcinoma); Anus Neoplasms (Anul Carcinoma)